Maternal morbidity and mortality due to placenta accreta spectrum disorders. (April 2021) - Fonseca, Andreia; Ayres de Campos, Diogo
Abstract: Placenta accreta spectrum (PAS) disorders are an increasing health problem in many parts of the world. They are an important risk factor for adverse maternal outcomes related to delivery, with a reported 18-fold increase in maternal morbidity. Profuse haemorrhage after attempting to remove the placenta is the most frequent complication and can lead to major maternal morbidity and ultimately to maternal death. Morbidity can also arise from the multiple procedures required to treat PAS disorders. Intensive care unit admission, mechanical ventilation, infection, and prolonged hospitalization are common in these patients. Long-term complications related to infertility and psychological disturbances can also occur and may have a strong and long-lasting impact on women's health. Antenatal diagnosis allows for appropriate scheduling of delivery and referral to a specialized centre and has been shown to reduce maternal morbidity and mortality. Highlights: Placenta accreta spectrum disorders are important risk factors for adverse outcomes. Haemorrhage after attempts to remove the placenta is the most frequent complication. Long-term morbidity includes psychological disorders and infertility. Planned management by specialized teams can improve prognosis.